Suboptimal Inspiratory Flow Rates Are Associated with Chronic Obstructive Pulmonary Disease and All-Cause Readmissions - Loh, Chee H.; Peters, Stephen P.; Lovings, Tina M.; Ohar, Jill A. (Annals of the American Thoracic Society, 2017)
Dry powder inhalers (DPIs) are prescribed after hospitalization for acute exacerbation of COPD (AECOPD). Peak inspiratory flow (PIF) affects DPI delivery. To study the impact of PIF on readmission after hospitalization for AECOPD. A retrospective analysis of hospitalized patients, enrolled in an AECOPD care plan, was performed. Data analyzed included PIF, age, sex, length of stay, Charlson Comorbidity Index, COPD Assessment Test score, modified Medical Research Council score, percent predicted FEV , FVC, and inspiratory capacity. A PIF equal to and less than 60 L/min was defined as suboptimal (sPIF). Outcome measures included 30- and 90-day COPD and all-cause readmissions, and days to next COPD and all-cause readmissions. Of the 123 subjects, 52% (n = 64) had sPIF. They had greater COPD Assessment Test scores (29.1 ± 5.9 vs. 25.3 ± 8.7; P = 0.0073), rates of 90-day COPD readmissions (28.1 vs. 13.6%; P = 0.048), fewer median days to COPD (63.5 [interquartile range (IQR), 21-89.8] vs. 144 [IQR, 66-218]; P = 0.002) and all-cause readmissions (65.5 [IQR, 24.3-107.3] vs. 101 [IQR, 54.5-205.5]; P = 0.009). PIF was the only variable (P = 0.041) that predicted days to COPD readmission in a multivariate model incorporating age, sex, percent predicted FEV , Charlson Comorbidity Index, and inspiratory flow group. In a group of patients with sPIF (n = 22), all-cause and COPD 30- and 90-day readmission rates were significantly lower for those discharged with nebulizer compared with DPI therapy. sPIF is common during AECOPD and predicts all-cause and COPD readmissions. Patients with sPIF may benefit from nebulized therapies. We recommend checking PIF in patients hospitalized for AECOPD for selection of delivery devices.